Nodular lesions of the skin. Granuloma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 1999)
Tick bite. Tick bite is always responsible for a cutaneous lesion. The latter ranges from an inflammatory papule to a granulomatous lesion, till to a gangrenous and then ulcerated lesion of various size. Other manifestations can be associated to tick bite such as those ones caused by toxic products of the tick (ascending flaccid palsy), the reactive manifestations against tick allergens and, finally, the manifestations caused by the tendency of the tick to be carrier of infectious agents of various type such as viruses, rickettsiae and spirochetae. However, we are not dealing in this chapter with the cutaneous and extracutaneous manifestations associated with tick bite. (...).